WAKF and Other Sister Concepts: Symbols of Islamic Philanthropy: Exploring the features and distinctions of WAKF and its sister concepts in Islamic philanthropy (Journal of Advances and Scholarly Researches in Allied Education, 2013)
Foundation of WAKF is religion arranged. Muslim WAKF has its own particular highlights. In spite of the fact that there are sure regular components in WAKF and its sister ideas like Gift, Sadquah, Trust, Charitable blessings and Evacuee property yet at the same time WAKF has its own remarkable highlights like of religious or devout rationale, changeless nature and use of usufruct, as devotion of property with mainstream thought process is blessing or Trust yet not WAKF. WAKF is a changeless gift. Any devotion which is devout however not of changeless nature is Sadqah but rather isn't WAKF as in it the dedicator will have no privilege in the property. A definitive advantage of it ought to go to the humanity. The fundamental motivation behind a WAKFs is religious, devout, or magnanimous. Sadly, the Indian Courts have neglected this very part of WAKFs, however the idea of WAKF was presented in India simply after the entry of Muslims. A few records where Muslim effect or impact was prevail divulges that the articulation WAKF was acquainted with express commitment. The commitment may likewise be made with the end goal of Settler's family, kids and relatives as this is the obligatory prerequisite for the legitimacy of a WAKF. In this article the specialist attempted to recognize the term 'WAKF' from its sister idea terms.